Advances in production of bioplastics by microalgae using food waste hydrolysate and wastewater: A review - Chong, J.W.R. (Elsevier Ltd, 2021)
Microalgae have emerged as an effective dual strategy for bio-valorisation of food processing wastewater and food waste hydrolysate which favours microalgae cultivation into producing value-added by products mainly lipids, carbohydrates, and proteins to the advantages of bioplastic production. Moreover, various microalgae have successfully removed high amount of organic pollutants from food processing wastewater prior discharging into the environment. Innovation of microalgae cultivating in food processing wastewater greatly reduced the cost of wastewater treatment compared to conventional approach in terms of lower carbon emissions, energy consumption, and chemical usage while producing microalgae biomass which can benefit low-cost fertilizer and bioplastic applications. The study on several microalgae species has all successfully grown on food waste hydrolysates showing high exponential growth rate and biomass production rich in proteins, lipids, carbohydrates, and fatty acids. Multiple techniques have been implemented for the extraction of food wastes to be incorporate into the bioplastic production. Â© 2021 Elsevier Ltd